Grid Middleware and Services - Talia, Domenico (Springer, 2017)
Grid Middleware and Services: Challenges and Solutions is the eighth volume of the CoreGRID series. The CoreGrid Proceedings is the premiere European event on Grid Computing. This book aims to strengthen and advance scientific and technological excellence in the area of Grid Computing. The main focus in this volume is on Grid middleware and service level agreement.